Prior Therapy With Pegylated-Interferon Alfa-2b Improves the Efficacy of Adjuvant Pembrolizumab in Resectable Advanced Melanoma - Jia, Dong-Dong; Niu, Yanling; Zhu, Honglin; Wang, Sizhen; Ma, Tonghui; Li, Tao (Frontiers in Oncology, 2021)
Combination immunotherapy can overcome the limited objective response rates of PD-1 blockade. Interferon alpha (IFN-α) has been proven to be effective in modulating immune responses and may enhance the clinical responses to PD-1 blockade. According to clinical practice guidelines, IFN-α was recommended as adjuvant therapy for stage IIB/C melanoma patients. However, the impact of prior IFN-α therapy on the efficacy of subsequent PD-1 blockade in melanoma has not been previously reported. Therefore, we performed a retrospective analysis for melanoma patients and addressed whether prior IFN-α therapy enhanced adjuvant pembrolizumab as later-line treatment. Fifty-six patients with resectable stage III/IV melanoma who received adjuvant therapy with pembrolizumab were retrospectively enrolled in this study. Notably, 25 patients received adjuvant pegylated IFN-α (PEG-IFN-α) in the prior line of treatment while 31 patients did not receive prior PEG-IFN-α therapy. Cox regression analysis showed that prior PEG-IFN-α therapy was associated with the efficacy of later-line adjuvant pembrolizumab (hazard ratio=0.37, 95% CI 0.16-0.89; P = 0.026). The recurrence rates after treatment with adjuvant pembrolizumab were significantly reduced in the prior PEG-IFN-α group (P < 0.001). The Kaplan-Meier analysis also showed that recurrence-free survival (RFS) after adjuvant pembrolizumab therapy was prolonged by prior PEG-IFN-α treatment (median RFSPem 8.5 months vs. 4.5 months; P = 0.0372). These findings indicated that prior PEG-IFN-α could enhance the efficacy of adjuvant pembrolizumab. The long-lasting effects of PEG-IFN-α provide a new rationale for designing combination or sequential immunotherapy.